BISNIS INVESTASI ONLINE DI WWW.PROFITCLICKING.COM PERSPEKTIF HUKUM ISLAM - Juliana Niswah (Maliyah : Jurnal Hukum Bisnis Islam, 2016)
The phenomenon of investment business today is extremely diverse including by their investment business deals with the online system. One of the investment vehicles online is a website berdomain Profit Clicking. Members depositing their funds (dollars) to the website berdomain Profit Clicking then the funds they will be processed so that they will get 3% for each day in the specified time, The length of time is adjusted to the funds they deposited. This paper discusses the cooperation agreement between the member and the Profit Clicking, profit and loss sharing system members, and the perspective of Islamic law against such investments. Gains derived member is calculated by the percentage based on the ad package owned by the member and the percentage of programs that followed members. Instead of a percentage of the profits of the company, the benefits seem flat because it has been set in advance. Profit Clicking cooperation in the perspective of Islamic law is considered illegitimate because of the many elements of obscurity (gharar) in the system. Members do not have rights and are not able to submit complaints to the agency any loss due to loss of payment to the member rights fully.